Malaysian Judicial Appointment Process: An Overview of the Reform - Shuaib, Farid Sufian (http://www.aensionline.com/jasr/jasr/2011/2273-2278.pdf, 2011)
The Federal Constitution of Malaysia provides for an executive centric mechanism in judicial appointment where the Prime Minister has the final say. To make matter worse for this executive dominance, a commission of enquiry found that parties that should not have a say in judicial appointment managed to drown the Chief Justice’s voice in proposing names of candidates to the Prime Minister. The finding of this commission compelled the government to form a Judicial Appointment Commission in improving the independence,integrity and accountability of the judiciary. This article seeks to examine the impetus of this reform and to explore the suitability of the principles adopted in the working of the Commission to achieve the stated objectives.